Trends and centre-to-centre variability in survival rates of very preterm infants (<32 weeks) over a 10-year-period in Switzerland. Issue 5 (29th August 2012) - Berger, Thomas M; Steurer, Martina A; Woerner, Andreas; Meyer-Schiffer, Philipp; Adams, Mark; ,
Abstract : Background: The publication of Swiss guidelines for the care of infants at the limit of viability (22–25 completed weeks) was followed by increased survival rates in the more mature infants (25 completed weeks). At the same time, considerable centre-to-centre (CTC) differences were noted. Objectives: To examine the trend of survival rates of borderline viable infants over a 10-year-period and to further explore CTC differences. Design: Population-based, retrospective cohort study. Setting: All nine level III neonatal intensive care units (NICUs) and affiliated paediatric hospitals in Switzerland. Patients: 6532 preterm infants with a gestational age (GA) <32 weeks born alive between 1 January 2000 and 31 December 2009. Main outcome measures: Trends of GA-specific delivery room and NICU mortality rates and survival rates to hospital discharge were assessed. For CTC comparisons, centre-specific risk-adjusted ORs for survival were calculated in three GA groups: A: 23 0/7 to 25 6/7 weeks (n=976), B: 26 0/7 to 28 6/7 weeks (n=1943) and C: 29 0/7 to 31 6/7 weeks (n=3399). Results: Survival rates of infants with a GA of 25 completed weeks which had improved from 42% in 2000/2001 to 60% in 2003/2004 remained unchanged at 63% over the next 5 years (2005–2009). Statistically significant CTC differences have persisted and are not restricted to borderline viable infants. Conclusions: In Switzerland, survival rates of infants born at the limit of viability have remained unchanged over the second half of the current decade. Risk-adjusted CTC outcome variability cannot be explained by differences in baseline demographics or centre case loads.